2018
DOI: 10.1667/rr15035.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Soft Tissue Sarcoma Cell Radiosensitivity by Poly(ADP-ribose) Polymerase-1 Inhibitors

Abstract: Soft tissue sarcomas (STS) are aggressive tumors with a poor prognosis. Poly(ADP-ribose) polymerase (PARP)-1 inhibitors (PARPi) enhance the cytotoxic effects of radiation. In this study, we evaluated the effect of PARPi on survival and DNA damage of irradiated STS cells. For clonogenic assays, STS cell lines were irradiated with or without olaparib, iniparib or veliparib pretreatment. The effect of PARP inhibition on γ-H2AX and Rad51 foci formation, on PARP-1, phospho-ERK and cleaved caspase-3 protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…2a). These observations are in agreement with data very recently reported by Mangoni et al (2018). In the present study we examined in detail the molecular mechanisms of PARPi effects on cell cycle progression and survival.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…2a). These observations are in agreement with data very recently reported by Mangoni et al (2018). In the present study we examined in detail the molecular mechanisms of PARPi effects on cell cycle progression and survival.…”
Section: Discussionsupporting
confidence: 94%
“…Only very recently, Mangoni et al have shown that pretreatment with Olaparib, Iniparib or Veliparib, three PARP1 inhibitors, is able to induce a significant radiosensitization in different soft tissue sarcoma cell lines (Mangoni et al 2018). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent trials are testing whether PARPi is effective in combination with radiation in squamous cell carcinoma (48) (NCT02229656), locally advanced rectal cancer (NCT02921256 and NCT01589419), high grade gliomas (NCT03212742), non-small cell lung cancer (NCT01386385 and NCT02412371), and soft tissue sarcoma (NCT02787642; ref. 49). Thus, although this study is the first to report that PARP inhibition may be an effective strategy in patients with IBC, the concept of PARP inhibitor-mediated radiosensitization is being explored in many other cancer contexts.…”
Section: Discussionmentioning
confidence: 95%
“…Olaparib (inhibitor of PARP 1/2) and AZD2461 (inhibitor of PARP 1/2/3) resulted in a reduction in growth at clinically achievable concentrations (1-5 µM olaparib and 5-10 µM AZD2461); however, talazoparib (inhibitor of PARP 1/2) was not effective against FP-RMS or FN-RMS [26,29,30]. Preclinical combination studies in RMS have shown that PARP inhibitors can enhance the efficacy of topoisomerase II inhibitors, ionizing radiation, and alkylating agents such as temozolomide [26,29,31,32]. The combination of olaparib with temozolomide was particularly effective when tested in mouse and zebrafish xenografts [33].…”
Section: Poly-adp-ribose Polymerase Inhibitors In Combination With Cytotoxic Agentsmentioning
confidence: 99%